Modern Aspects of Etiopathogenetic Treatment of Ophthalmodemodicosis (Literature Review) - A. D. Chuprov; E. K. Malgina (Oftalʹmologiâ, 2018)
Demodicosis is one of most spread dermatosis. Blepharitis of Demodectic etiology occupy from 39 to 88% among all inflammatory diseases of the eyelids. The disease is widespread, 89% of patients are parasite carriers, despite the fact that most of them do not feel any manifestations of this pathology. The effect of predisposing factors such as chronic diseases of the gastrointestinal tract and liver, endocrine pathology, undernutrition, unhealthy habits etc. promote the development of Demodicosis. According to some authors, the mite of Demodex genus is a potentially pathogenic saprophyte microorganism, showing its pathogenic activity under certain conditions. According to Russian studies, infection with Demodex is up to 92%, but it is not always Demodicosis, the manifestations of it depend not only on the number of individuals, but also on the state of immunodefence. In recent years, cases of mite detection in humans have increased. Perhaps, this is facilitated by the environmental problem associated with environmental pollution, including air pollution, and the growth of chronic diseases, especially digestive diseases, endocrine diseases — diabetes mellitus. The reason for this, as a rule, is an unhealthy way of life and nutrition. Despite the variety of drugs with specific and symptomatic effect, the treatment of eye Demodicosis is ineffective. This is caused by the duration of therapy, noncompliance of treatment and hygiene standards, the prescription of symptomatic drugs that do not have acaricidal action, the lack of chronic diseases treatment, and the need for comprehensive treatment of eye Demodicosis by an ophthalmologist and facial skin — by a dermatologist. The lack of knowledge of etiopathogenesis and the insufficient effectiveness of Demodex therapy methods contribute to its chronically recurrent course with impairment of the severity of clinical manifestations and are a significant psychotraumatic factor for patients that leads to the development of psychoasthenic state and neuroses and indicates the medico-social significance of the problem of this Dermatosis.